Wind Energy Control Technologies for Power Quality Improvement on a Microgrid-A Review - Hassan, Kabiru A.; Ajewole, Titus O.; Olukayode, Olakunle; Agboola, Mutiu K. (Emerging Advances in Integrated Technology, 2025)
This paper focuses on the development of wind energy control technologies in hybrid energy systems, highlighting their crucial role in integrating renewable energy sources on a microgrid. It examines the wind turbine curve, a fundamental framework for wind turbine operation, and the challenges and possibilities of integrating wind power into renewable energy systems, various methods to improve the efficiency and stability of wind turbines, with wind turbine control methods as the cornerstone. The study also examines the qualities of advanced wind turbine controllers, highlighting their efficiency in using wind energy resources and investigates wind energy conversion systems (WECSs) electrical generators, highlighting current developments that promise increased energy production and system dependability. The aim is to contribute to the ongoing discussion on wind energy control technologies by utilizing various cutting-edge studies. The study aims to provide valuable insights and views that can guide the energy industry toward a sustainable and environmentally friendly future through a comprehensive assessment of these crucial components.